Cellular responses of Pacific oyster (Crassostrea gigas) gametes exposed in vitro to polystyrene nanoparticles. (October 2018) - González-Fernández, Carmen; Tallec, Kevin; Le Goïc, Nelly; Lambert, Christophe; Soudant, Philippe; Huvet, Arnaud; Suquet, Marc; Berchel, Mathieu; Paul-Pont, Ika
Abstract: While the detection and quantification of nano-sized plastic in the environment remains a challenge, the growing number of polymer applications mean that we can expect an increase in the release of nanoplastics into the environment by indirect outputs. Today, very little is known about the impact of nano-sized plastics on marine organisms. Thus, the objective of this study was to investigate the toxicity of polystyrene nanoplastics (NPs) on oyster ( Crassostrea gigas ) gametes. Spermatozoa and oocytes were exposed to four NPs concentrations ranging from 0.1 to 100 mg L −1 for 1, 3 and 5 h. NPs coated with carboxylic (PS-COOH) and amine groups (PS-NH2 ) were used to determine how surface properties influence the effects of nanoplastics. Results demonstrated the adhesion of NPs to oyster spermatozoa and oocytes as suggested by the increase of relative cell size and complexity measured by flow-cytometry and confirmed by microscopy observations. A significant increase of ROS production was observed in sperm cells upon exposure to 100 mg L −1 PS-COOH, but was not observed with PS-NH2, suggesting a differential effect according to the NP-associated functional group. Altogether, these results demonstrate that the effects of NPs occur rapidly, are complex and are possibly associated with the cellular eco-corona, which could modify NPs behaviour and toxicity. Highlights: Nanoplastics attach to both oocytes and spermatozoa. Cellular impacts of NPs was observed on spermatozoa. PS-COOH exposure generated a dose-response increase in ROS production in spermatozoa. Higher impact of PS-COOH suggest an influence of particle surface properties.